SINTESIS DAN KARAKTERISASI SUPERABSORBEN DARI SELULOSA JERAMI PADI (Superabsorbent Synthesis and Characterization of Rice Straw Cellulose) - Wina Yulianti; Farida Laila (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2014)
Copolymerization of cellulose from rice straw with acrylic acid and acrylamide produce biopolymer superabsorbent. Cellulose was purified from fat content by extraction with toluene:ethanol (2:1). Hemicelluloses and lignin were removal by using potassium hydroxide 5% and hydrogen peroxide 2% at alkaline pH. Cellulose yield obtained was 21.56%. FTIR spectra of lignin showed a loss of absorption at 1728 cm-1. Copolymerization was carried out at 65 C under nitrogen athmosphere. Initiator and cross linking agent used were potassium peroxodisulfate and N'N-methylene bis acrylamide. Superbasorben resulted from this experiment showed the water swelling capacity after 24 hour for the water, solution of 100 ppm of ammonium chloride, and urea respectively 387,11 g/g ; 193,47 g/g and 400,17 g/g.Keywords : superabsorbent, rice straw, swelling capacity